Hubungan Kecemasan dengan Kelelahan Kerja pada Pekerja Perusahaan X Menggunakan Depression Anxiety Stress Scale-21 (DASS-21) - Tamara, Xenia; Hadiyanto; Gunterus Evans; Evi Ulina Margareta Situmorang (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: One of the common psychological disorders experienced by workers that can affect both health and performance is anxiety. Research has shown that anxiety is connected to higher levels of work fatigue. Among industrial workers, one of the major risk factors for occupational accidents is work fatigue. Purpose: This study aims to measure not only the levels of anxiety but also work fatigue, as well as analyze the correlation between anxiety and work fatigue among employees of company X. Methods: This research employed a cross-sectional design with a total of 137 employees of company X as participants. Consecutive sampling was used as a sampling technique, and data were obtained through the use of questionnaires from September 2024 - October 2025. Both univariate and bivariate analysis (Chi-square test) were used to examine the data. Results: The finding showed that prevalence of anxiety was 40.15% and work fatigue was 37.23%, and there was a significant correlation between anxiety and work fatigue (p < 0.001). Conclusion: In conclusion, there is a significant association between anxiety and work fatigue among employees of company X. Future research may employ a longitudinal design to determine causal relationships, and include workers from various industrial sectors. The findings may benefit companies and policymakers in understanding the influence of mental health factors on work fatigue. Previous studies have largely focused on online motorcycle taxi drivers and healthcare workers, while studies involving company employees remain limited.